IMPLEMENTASI KEBIJAKAN PENGELOLAAN WILAYAH PESISIR PADA KAWASAN PEMANFAATAN UMUM DAN KONSERVASI KOTA SEMARANG - Sarani, Diyan Valentina Putri; Dwimawanti, Ida Hayu; Hidayat, Zainal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The implementation of policies on the management of coastal in the area of general used and conservation at semarang is planning coordination, utilization, monitoring, and control of coastal resources of the Government and Local Government, between sectors, between terrestrial and marine ecosystems, as well as between science and management to improve the welfare of the people. The purpose of this research is to analyze Policy For Coastal Management Policy Implementation in the region common Utilization and Conservation Semarang with 5 indicators that can be used to assess the quality of policy output, namely Access, Coverage, Frequency, Service Delivery and Accountability. Researchers analyzed factors that support and hinder the implementation of coastal zone management policy with 4 factors was found in the field. 4 factors are environmental, Technology, program plan and Socio economic Conditions. The results of this research is that the implementation of policies on the management of coastal in the area of general used and conservation at semarang is good enough but still not optimal, because there are 3 indicators are encountering many obstacles for the Implementation. Still need for improvement in indicators Access, Coverage and Frequency.